Factors Influencing the Seasonal Patterns of Infectious Diseases - Fares, Auda (Medknow Publications & Media Pvt Ltd, 2013)
The recognition of seasonal patterns in infectious disease occurrence dates back at least as far as the hippocratic era, but the mechanisms underlying these fluctuations remain poorly understood. Many classes of mechanistic hypotheses have been proposed to explain seasonality of various directly transmitted diseases, including at least the following; human activity, seasonal variability in human immune system function, seasonal variations in vitamin D levels, seasonality of melatonin, and pathogen infectivity. In this short paper will briefly discuss the role of these factors in the seasonal patterns of infectious diseases.